EFEKTIVITAS PENERAPAN PERILAKU CINTA TANAH AIR PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN 8 BUNOBOGU (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This thesis discusses the effectiveness of implementing patriotic behavior in the learning of Pancasila Education for fifth grade students at SDN 08 Bunobogu. The research problems are formulated as follows: (1) How effective is the implementation of patriotic behavior in Pancasila Education learning in the fifth grade of SDN 08 Bunobogu? (2) What aspects of practicing patriotic behavior serve as supporting factors, obstacles, and challenges for teachers and students in applying it within the school environment of SDN 08 Bunobogu? The purpose of this study is to analyze the extent to which patriotic behavior is applied in Pancasila Education learning for fifth grade students at SDN 08 Bunobogu. This study employed a qualitative research design, with data collected through documentation, interviews, and observation. Data analysis techniques included data reduction, presentation, findings, and verification. The results indicate that the implementation of patriotic behavior in Pancasila Education at SDN 08 Bunobogu remains less effective. Several obstacles were identified, including the low level of student nationalism, limited school facilities, and curriculum changes that have not been matched with adequate teacher readiness. Supporting factors include routine school activities, the role of teachers, and parental support. However, hindering factors consist of inadequate facilities, lack of parental involvement, and absence of government assistance, while the main challenge is the regulation within the Merdeka Curriculum. The researcher suggests improvements in school facilities, teacher competencies, and more active parental involvement.